2006
DOI: 10.1055/s-2006-924120
|View full text |Cite
|
Sign up to set email alerts
|

Integration of Abscisic Acid Signalling into Plant Responses

Abstract: The phytohormone abscisic acid (ABA) plays a major role as an endogenous messenger in the regulation of plant's water status. ABA is generated as a signal during a plant's life cycle to control seed germination and further developmental processes and in response to abiotic stress imposed by salt, cold, drought, and wounding. The action of ABA can target specifically guard cells for induction of stomatal closure but may also signal systemically for adjustment towards severe water shortage. At the molecular leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
164
0
5

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 220 publications
(171 citation statements)
references
References 158 publications
(168 reference statements)
2
164
0
5
Order By: Relevance
“…In the heterogeneous treatments, although each compartment was subjected to independent treatment, the two parts of the root system showed similar root ABA concentration (Table 3) probably because of ABA redistribution among tissues (Christmann et al 2006). Consistent with the effects of mycorrhizal inoculation on ABA production in the homogeneous treatments, both nM-M and M-M significantly decreased ABA concentration under drought stress (Table 3).…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…In the heterogeneous treatments, although each compartment was subjected to independent treatment, the two parts of the root system showed similar root ABA concentration (Table 3) probably because of ABA redistribution among tissues (Christmann et al 2006). Consistent with the effects of mycorrhizal inoculation on ABA production in the homogeneous treatments, both nM-M and M-M significantly decreased ABA concentration under drought stress (Table 3).…”
Section: Discussionsupporting
confidence: 66%
“…Consistent with the effects of mycorrhizal inoculation on ABA production in the homogeneous treatments, both nM-M and M-M significantly decreased ABA concentration under drought stress (Table 3). The physiological activity of ABA is related not only to its biosynthesis and transport but also to sensitivity of target structures (Christmann et al 2006). In this study, the target structure was the above-mentioned PC that interacted with ABRE motifs in IPS, because the results obtained from the homogeneous treatments showed that cooperation of IPS and 14-3GF potentially steered a positive effect on AM plant drought tolerance.…”
Section: Discussionmentioning
confidence: 94%
“…ABA is a major regulator of abiotic stress responses caused by drought, salt, cold and wounding (Christmann et al ., 2006; Raghavendra et al ., 2010), and also plays a prominent role in plant resistance to biotic stresses such as pathogen attack (Ton et al ., 2009; Denance et al ., 2013) and herbivorous insects (Bodenhausen and Reymond, 2007; Verhage et al ., 2011; Pineda et al ., 2012; Lazebnik et al ., 2014). In our study, ABA content was increased in the Arabidopsis leaves when it was inoculated with T. gamsii F18.…”
Section: Discussionmentioning
confidence: 99%
“…The phytohormone abscisic acid (ABA), a wellrecognized stress hormone, is up-regulated to turn on stress response genes in cells to help plants cope with unsuitable environments (Christmann et al, 2006;Yamaguchi-Shinozaki and Shinozaki, 2006;Qin et al, 2011). For example, osmotic stress stimulates the biosynthesis and accumulation of ABA in guard cells (Yamaguchi-Shinozaki and Shinozaki, 2006).…”
mentioning
confidence: 99%